Autodeterminación y acceso a la educación superior en personas con discapacidad - Toro Flores, Markus Pavelko (Machala : Universidad Técnica de Machala, 2018)
The study of self-determination and access to higher education in persons with disabilities, focuses on determining the personal and contextual factors that allow or hinder the access and / or permanence of students with Special Educational Needs, in Higher Education. The work is based on the integrative approach which values the biological and sociocultural characteristics that are evident in the cognitive, behavioral, affective and interpersonal manifestations of the individual. The categories of analysis were: self-determination-disability and higher education. Three students participated in the study; two women and one man, with their respective family representatives, and four authorities belonging to the Academic Unit of Social Sciences of the Technical University of Machala. This research was based on the mixed approach (qualitative and quantitative) is based on the narrative design specifically autobiographical, trying to collect information on stories and experiences in relation to the subject based on the set of testimonials about realities, events , attitudes, among other aspects. The techniques and instruments used were the semi-structured interview on the sample classified for students, structured by four questions, focused on issues of self-determination, support and obstacles encountered in accessing and remaining in Higher Education; to parents, composed of four questions and inquires about aspects related to coping with their child's disability and factors influencing the development of self-determination; and to the authorities, which consists of three questions, which address issues related to the access and permanence of students with Educational Needs in Higher Education. In addition, the ARC-INICO Self-Determination Evaluation Scale was used, which assesses the level of each dimension: autonomy, self-regulation, empowerment, and self-knowledge and the global level of self-determined behavior, granting a full assessment of the strengths and weaknesses of young students of different nature of disability
El estudio de autodeterminación y acceso a la educación superior en personas con discapacidad, se centra en determinar los factores personales y contextuales que permiten u obstaculizan el acceso y/o permanencia de los estudiantes con Necesidades Educativas Especiales, en la Educación Superior. El trabajo se sustenta en el enfoque integrativo el cual valora las características biológicas y socioculturales que se evidencian en las manifestaciones cognitivas, conductuales, afectivas e interpersonales del individuo. Las categorías de análisis fueron: autodeterminación y educación superior. En el estudio participaron tres estudiantes; dos mujeres y un varón, con sus respectivos representantes de familia, y cuatro autoridades pertenecientes a la Unidad Académica de Ciencias Sociales de la Universidad Técnica de Machala. La presente investigación se realizó en base al enfoque mixto (cualitativo y cuantitativo) se fundamenta en el diseño narrativo concretamente de tipo autobiográfico, pretendiendo recolectar información sobre historias y experiencias acaecidas con relación al sujeto basándose en el conjunto de testimonios vivenciales acerca de realidades, sucesos, actitudes, entre otros aspectos. Las técnicas e instrumentos utilizados fueron la entrevista semiestructurada sobre la muestra clasificada para estudiantes, estructurada por cuatro preguntas, enfocadas en temas de autodeterminación, el apoyo y los obstáculos encontrados en el acceso y permanencia a la Educación Superior; a padres de familia, compuesta de cuatro preguntas e indaga sobre aspectos relacionados al afrontamiento de la discapacidad de su hijo y factores de influencia en el desarrollo de autodeterminación; y a las autoridades, el cual consta de tres preguntas, que aborda temáticas relacionadas con el acceso y permanencia de los estudiantes con Necesidades Educativas en la Educación Superior. Además, se utilizó la escala ARC-INICO de Evaluación de Autodeterminación, que evalúa el nivel de cada dimensión: autonomía, autorregulación, empoderamiento, y autoconocimiento y el nivel global del comportamiento autodeterminado concediendo una valoración completa de las fortalezas y debilidades a jóvenes estudiantes de diferente índole de discapacidad.
Keywords: AUTODETERMINACION; ACCESO; EDUCACION SUPERIOR; DISCAPACIDAD